Progression-free survival as a surrogate endpoint for overall survival in antibody-drug conjugate trials for advanced breast cancer: a systematic review and meta-analysis - Almeida, Luiz Felipe Costa de; Silva, Luís Felipe Leite da; Conceição, Lucas Diniz da; Cappellaro, Anelise Poluboiarinov; Araújo, Cissa Isabella Coelho; Lopes, Caio Silva; Silva, Jesse Lopes da (Mastology, 2026)
Objective: To evaluate the validity of progression-free survival (PFS) as a surrogate endpoint for overall survival (OS) in randomized controlled trials assessing antibody-drug conjugates in advanced breast cancer. Methods: A systematic review and meta-analysis was performed following the Preferred Reporting Items for Systematic reviews and MetaAnalyses (PRISMA) guidelines. Searches were conducted on PubMed, Embase, and Cochrane databases, including conference proceedings up to February 2024. Linear regression models weighted by trial size assessed trial-level correlation between hazard ratios for PFS and OS. Surrogacy strength was classified based on the coefficient of determination (R²): strong (≥0.7), moderate (0.5–0.69), or weak (<0.5). Results: Fifteen randomized controlled trials involving 7,360 patients were included. Overall, a moderate correlation between PFS and OS was identified (R²=0.61; 95% confidence interval [CI] 0.29–0.94). Subgroup analyses revealed variability, with a notably weak correlation in human epidermal growth factor receptor-type 2 (HER2)-positive breast cancer (R²=0.31; 95%CI 0.00–1.00). Trials with fewer participants (≤529) exhibited stronger correlations (R²=0.74; 95%CI 0.35–1.00) compared to larger studies (>529 participants; R²=0.36; 95%CI 0.00–1.00). The surrogate threshold effect for meaningful OS prediction was identified as a 25% reduction in the hazard ratio for PFS across trials. Conclusion: PFS showed moderate surrogacy for OS in antibody-drug conjugate trials for advanced breast cancer, with substantial variation across subgroups. Given the weak correlation in HER2-positive disease, reliance solely on PFS might misrepresent true clinical benefit. OS should remain the primary endpoint in trials evaluating antibodydrug conjugate efficacy.